Business intelligence system using goal-ontology approach: A case study in Universiti Utara Malaysia - Ta'a, Azman (2014)
Business Intelligence(BI) system design involves several tasks such as d e-fining DW requirements, modeling DW structure and specifying ETL processes operations, and these have been studied and practiced for many years.However, the common design-related problems such as defining user re-quirements and deriving data integration and transformation activities are still far from being resolved due to the ambiguity of business requirements and the complexity of DW and ETL process, and that was the fundamental issues of conflicts in heterogeneous information sharing environments.Current approaches that are based on existing software requirement methods still have limitations on reconciliation the business semantics for BI re-quirements toward the modeling of DW and ETL process structure.This will difficult the process to define the DW and ETL process specifications accordingly.This paper adopts the Requirement Analysis Method for ETL Processes (RAMEPs) framework for the BI system approach and focused on requirement analysis method for designing the DW schemas and ETL process specifications.The RAMEPs is based on ontology and goal-driven approach in analyzing the business requirements and modeling the data integration and transformation activities.A case study of the student affair in University domain is used to illustrate how the BI approach can be implemented.